2011
DOI: 10.1002/jtr.879
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Word of Mouth and Revisit Intentions to Rural Tourism Destinations: a Case of North Dakota, USA

Abstract: Destination managers in rural states, like North Dakota, understand the benefits of tourism and, thus, the importance of studying visitors' intentions. This study investigated visitors' perceptions of destination image, value and satisfaction and those variables' relationship with future behaviors, with a specific focus on their intent to return and make recommendations to others. The results showed that destination image directly affects visitors' perception of value and revisit intentions, and it indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 60 publications
(73 reference statements)
5
99
1
7
Order By: Relevance
“…They concluded that destination image positively affects destination attachment and overall satisfaction. Phillips et al (2013) also found that destination image directly influences trip perceived value and revisit intention, and it indirectly influences tourist overall satisfaction and intention to recommend. Sun, Chi, and Xu (2013) also found that destination image has a significant and positive impact on trip perceived value and tourist satisfaction.…”
Section: The Role Of Destination Image In the On-travel And Post-travmentioning
confidence: 93%
See 1 more Smart Citation
“…They concluded that destination image positively affects destination attachment and overall satisfaction. Phillips et al (2013) also found that destination image directly influences trip perceived value and revisit intention, and it indirectly influences tourist overall satisfaction and intention to recommend. Sun, Chi, and Xu (2013) also found that destination image has a significant and positive impact on trip perceived value and tourist satisfaction.…”
Section: The Role Of Destination Image In the On-travel And Post-travmentioning
confidence: 93%
“…One of the powerful factors influencing tourists' decision-making behavior and the choice of destination is destination image (Assaker, Esposito Vinzi, & O'Connor, 2011;Bigné, Sánchez, & Sánchez, 2001;Chen & Tsai, 2007;Chen et al, 2013;Chi & Qu, 2008;Kozak & Decrop, 2009;Nicoletta & Servidio, 2012;Phillips, Wolfe, Hodur, & Leistritz, 2013;Sonmez & Sirakaya, 2002;Tavitiyaman & Qu, 2013). Destinations which have a positive and strong image are more likely to be chosen by tourists (Echtner & Ritchie, 2003;Tavitiyaman & Qu, 2013;Zahra, 2012) than those without.…”
Section: Iran and Its Image In The Worldmentioning
confidence: 96%
“…The reasons and motivations scale for one year of abroad study was based on Park and Njite [65]. The scale to measure image in tourist destination selection in the context of students´ mobility was based on Beerli, Palacio, Martıń [66], and Phillips et al [67]. The scale to measure the sources of information was based on Morais and Lin [49].…”
Section: Delphi Technique To Adapt the Scales Of Measurementioning
confidence: 99%
“…There are also recommendations on the importance of tourism destinations in maintaining a high level of satisfaction by offering services that make the most of the destination, as high satisfaction is an important factor in visitors engaging in positive WOM with potential visitors (Phillips, Wolfe, Hodur, & Leistritz, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%